Awareness and Attitude on Dyslexia among Primary School Teachers, Lalitpur - Shahi Thakuri, Bhawani; Subedi, Prasai, Durga (Journal of Nursing Education of Nepal, 2024)
Introduction: Dyslexia is the most common learning disorder in school-age children, affecting areas such as basic reading skills, and written expression, listening, and speaking significantly impacts children’s education, career, communication, and health. Teachers’ awareness and attitudes toward learning disabilities are crucial for timely diagnosis, preventing further mental and social damage through educational rehabilitation and treatment measures. The study aims to assess the awareness and attitudes regarding dyslexia among primary school teachers in selected schools of Lalitpur Municipality. Methods: This study employed a descriptive cross-sectional research design using a multistage cluster sampling method to select 180 participants from 30 public schools of Lalitpur Municipality. Ethical approval was obtained from the Institutional Review Committee of Tribhuvan University, Institute of Medicine. Data collection was conducted using a self-administered questionnaire from September 1 to 28, 2019. Data analysis involved both descriptive and inferential statistics. Results: Most of the respondents (88.3%) had an adequate level of awareness about dyslexia, and more than half (53.9%) had a positive attitude toward the disorder. A significant association was found between the level of awareness and religion (p-value 0.049), but no significant association with age, ethnic group, educational status, experience, class teaching, or subject teaching. Additionally, there was a significant association between attitude levels and age group (p-value 0.002) and educational level (p-value 0.001). Conclusion: Awareness of dyslexia among primary school teachers in Lalitpur is encouraging, comparingly only more than half of the teachers have positive attitude. So there is need to improve awareness and attitude among school-teachers.